Difficult cannulation as defined by a prospective study of the Scandinavian Association for Digestive Endoscopy (SADE) in 907 ERCPs. (June 2014) - Halttunen, Jorma; Meisner, Søren; Aabakken, Lars; Arnelo, Urban; Grönroos, Juha; Hauge, Truls; Kleveland, Per M.; Nordblad Schmidt, Palle; Saarela, Arto; Swahn, Fredrik; Toth, Ervin; Mustonen, Harri; et al.
Abstract Background. The definition of a "difficult" cannulation varies considerably in reports of endoscopic retrograde cholangiopancreatography (ERCP). Aims. To define a difficult cannulation, which translates into higher risk of post-ERCP pancreatitis. Patients and methods. Prospective consecutive recording of 907 cannulations in Scandinavian centers done by experienced endoscopists. Inclusion: indication for biliary access in patients with intact papilla. Exclusion: acute non-biliary and chronic pancreatitis at time of procedure. Results. The primary cannulation succeeded in 74.9%, with median values for time 0.88 min (53 s), with two attempts and with zero pancreatic passages or injections. The overall cannulation success was 97.4% and post-ERCP pancreatitis (PEP) rate was 5.3%. The median time for all successful cannulations was 1.55 min (range 0.02–94.2). If the primary cannulation succeeded, the pancreatitis rate was 2.8%; after secondary methods, it rose to 11.5%. Procedures lasting less than 5 min had a PEP rate of 2.6% versus 11.8% in those lasting longer. With one attempt, the PEP rate was 0.6%, with two 3.1%, with three to four 6.1%, and with five and more 11.9%. With one accidental pancreatic guide-wire passage, the risk of the PEP was 3.7%, and with two passages, it was 13.1%. Conclusions. If the increasing rate of PEP is taken as defining factor, the wire-guided cannulation of a native papilla can be considered difficult after 5 min, five attempts, and two pancreatic guide-wire passages when any of those limits is exceeded.